Rational Development of LEA29Y (belatacept), a High‐Affinity Variant of CTLA4‐Ig with Potent Immunosuppressive Properties - Larsen, Christian P.; Pearson, Thomas C.; Adams, Andrew B.; Tso, Paul; Shirasugi, Nozomu; StrobertM, Elizabeth; Anderson, Dan; Cowan, Shannon; Price, Karen; Naemura, Joseph; Emswiler, John; Greene, JoAnne; et al. (American journal of transplantation, 2005)
Current success in organ transplantation is dependent upon the use of calcineurin‐inhibitor‐based immunosuppressive regimens. Unfortunately, current immunotherapy targets molecules with ubiquitous expression resulting in devastating non‐immune side effects. T‐cell costimulation has been identified as a new potential immunosuppressive target. The best characterized pathway includes CD28, its homologue CTLA4 and their ligands CD80 and CD86. While an immunoglobulin fusion protein construct of CTLA4 suppressed rejection in rodents, it lacked efficacy in primate transplant models. In an attempt to increase the biologic potency of the parent molecule a novel, modified version of CTLA4‐Ig, LEA29Y (belatacept), was constructed. Two amino acid substitutions (L104E and A29Y) gave rise to slower dissociation rates for both CD86 and CD80. The increased avidity resulted in a 10‐fold increase in potency in vitro and significant prolongation of renal allograft survival in a pre‐clinical primate model. The use of immunoselective biologics may provide effective maintenance immunosuppression while avoiding the collateral toxicities associated with conventional immunsuppressants.